2006
DOI: 10.1111/j.1399-0039.2006.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of KIR genes in tuberculosis patients

Abstract: A total of 97 patients with tuberculosis (TB) and 51 controls from Xalapa, Veracruz, Mexico, were studied for the presence and absence of killer cell immunoglobulin-like receptor (KIR) genes. The number of patients with either KIR2DL1 or KIR2DL3 differed significantly compared with the controls. However, only the difference in KIR2DL3 remained significant after correction for the number of factors analysed. We also found KIR2DS2 with its presumed C1 group ligand less prevalent in TB patients than in the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 23 publications
(23 reference statements)
1
30
2
Order By: Relevance
“…KIR2DS1, 2DS3, and 3DS1 may serve as PTB susceptibility genes. Our results were inconsistent with data described by Mendez et al (2006) showing that KIR2DL3 is significant in patients compared with controls, however. The discrepancy can be explained by the fact that they investigated a different population-each population has a specific KIR distribution.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…KIR2DS1, 2DS3, and 3DS1 may serve as PTB susceptibility genes. Our results were inconsistent with data described by Mendez et al (2006) showing that KIR2DL3 is significant in patients compared with controls, however. The discrepancy can be explained by the fact that they investigated a different population-each population has a specific KIR distribution.…”
Section: Discussioncontrasting
confidence: 58%
“…According to data from Jiang et al (2005), the gene frequency of KIR2DL3 is more than 90% in the Chinese Han population; therefore, KIR2DL3 was not significant between groups in our present study. The sample size, diversity of technology used, linkage disequilibrium, and other limitations in our study design might also explain the discrepancy between our data and those of Mendez et al (2006).…”
Section: Discussioncontrasting
confidence: 53%
“…Our findings also indicated that two inhibitory genes, KIR2DL3 and KIR3DL1 may confer susceptibility to tuberculosis. Increase in KIR2DL3 expression augmented the inhibition of killer function of NK cells in TB [39,40]. The inhibitory KIRs (2DL and 3DL) are also known to bind to specific HLA molecules correlating with their ability to inhibit NK cytolysis of target cells bearing those HLA allotypes [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, Hanvesakul et al (6) HLA-C1 and -C2 groups were defined using two probes that differentiated nucleotides at positions 77 and 80 as previously described (8). ( Figure 1B …”
Section: In Contrast To Kidney Transplantation (4) Hla-matching For mentioning
confidence: 99%